PERAN DIVISI EVENT CREATIVE DALAM PELAKSANAAN PAKET EDUWISATA DI JEMBER MINI ZOO - Indraswari, Elsa Berliana (My University, 2025)
Jember Mini Zoo is one of the educational tourism destinations located in Jember, East Java. This destination offers various interactive and learning-based activities for school-aged children, especially those in kindergarten and elementary school. The implementation of educational tour packages at Jember Mini Zoo is supported by several divisions, including the Event Creative Division. The Event Creative Division is responsible for the preparation and execution of activities provided in the educational tour programs. These activities include interactive tours with animals, outbound games, and guided storytelling about animal species. The Event Creative Division is composed of staff responsible for preparation and tour guidance. Their duties include setting up equipment, guiding students through the zoo, explaining information about the animals, and managing outbound sessions. Coordination with other divisions such as marketing, ticketing, restaurant, and animal show is essential to ensure the program runs smoothly. The staff is also tasked with reporting daily preparations and conducting simple evaluations after each activity to improve the service quality. Throughout the educational tour, the division plays an important role in ensuring that all planned components are carried out properly. They are also required to adjust their communication styles based on the age group of visitors. Through creativity and collaboration, the Event Creative Division helps provide visitors with not only fun experiences but also meaningful educational value during their visit to Jember Mini Zoo.
Keywords: Educational Tourism; Event Creative Division; Jember Mini Zoo; Package; Role